About Calculation of Unified Module Recuperator (Module M-I and M-II) for Heating and Thermal Furnaces at Blanking and Machine Assembling Shops of Engineering, Automotive and Tractor Plants in Republic of Belarus - A. P. Nesenchuk; N. L. Mandel; V. N. Shishkov; G. S. Novgorodova; T. V. Ryzhova; M. G. Pshonik; A. R. Kachar (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper shows an influence of outside ribbing of heat-exchange surface of unified modules M-I and M-II on heat transfer factor of the proposed recuperator and its hydro-dynamic resistance.